2003
DOI: 10.1097/01.jom.0000091683.25325.55
|View full text |Cite
|
Sign up to set email alerts
|

Primary Congenital Hypothyroidism, Newborn Thyroid Function, and Environmental Perchlorate Exposure Among Residents of a Southern California Community

Abstract: The objectives of this study were to evaluate whether there were higher rates of primary congenital hypothyroidism (PCH) or elevated concentrations of thyroid-stimulating hormone (TSH) in a community where perchlorate was detected in groundwater wells. The adjusted PCH prevalence ratio and 95% confidence interval (CI) comparing the study community to San Bernardino and Riverside counties combined was 0.45 (95% CI=0.06-1.64). The odds ratios for elevated TSH concentration were 1.24 (95% CI=0.89-1.68) among all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
4
33
0
Order By: Relevance
“…This observation is in line with other cohort studies [30][31]. For example, Lawrence et al [30] demonstrated the sensitivity of the thyroid iodide trap to perchlorate in nine healthy men who were daily administered a dose of 10 mg perchlorate daily for 2 weeks, but also found that circulating concentrations of TH and TSH were not affected.…”
Section: Perchloratessupporting
confidence: 86%
“…This observation is in line with other cohort studies [30][31]. For example, Lawrence et al [30] demonstrated the sensitivity of the thyroid iodide trap to perchlorate in nine healthy men who were daily administered a dose of 10 mg perchlorate daily for 2 weeks, but also found that circulating concentrations of TH and TSH were not affected.…”
Section: Perchloratessupporting
confidence: 86%
“…Perchlorate levels in Las Vegas ranged between 9 and 15 lg/L during the study period while perchlorate levels in Reno were below the detection limit of 4 lg/L. Kelsh et al (2003), investigating a perchlorate exposed population in California, also found no increase in the odds ratio for either increased serum TSH or diagnosis of primary congenital hypothyroidism. Finally, Lamm and Doemland (1999) reported no elevation in the incidence of congenital hypothyroidism in seven California and Nevada counties where perchlorate was detected in drinking water wells.…”
Section: Discussionmentioning
confidence: 86%
“…Animal studies of these endpoints (e.g., alterations in the size of various brain structures, altered patterns of myelination, behavioral responses) have not been definitive with negative results in rabbits (York et al, 2001a,b) and contradictory findings in rats (Argus, 2001;York et al, 2001a,b). Ecological studies conducted in human populations (focusing on neonatal hormone levels rather than neurodevelopmental endpoints) have yielded generally negative findings (Crump et al, 2000;Kelsh et al, 2003;Lamm and Doemland, 1999;Li et al, 2000a,b) with one positive published study (Brechner et al, 2000). The animal and human data have been subject to considerable scrutiny and are currently the subject of vigorous debate.…”
Section: Disruption Of Thyroid Hormone Homeostasismentioning
confidence: 99%
“…Results are shown in Figure 1 of the current paper. 12) Kelsh et al [37]. This was an epidemiological study of the relationship between exposure to perchlorate in water and the incidence of primary congenital hypothyroidism in a population of 15,090 newborns in California.…”
Section: Epidemiological and Clinical Studies Databasementioning
confidence: 99%